A Political Ecology of Covid19 – Some reflections - Van Vossole, Jonas (2020)
Despite the renewed popularity of Foucault’s and Agamben’s concept of bio-politics to analyse the present crisis, I believe that the framework of Marxist political ecology – which in the last decade has gained considerable influence - offers us a more useful framework. Marxist political ecology considers capitalism not just as an economic or social system, but as a socio-ecology (Moore, 2011). Clashing with his German social-democratic contemporaries, Marx already pointed out that use value has two sources: nature and human labour. The purpose of existence of capital is profit. In the capitalist socio-ecology, capital accumulates through exploitation – based upon a legal framework of wage labour – and primary accumulation or expropriation – based upon the extra-legal framework of destruction, colonization and violence of what is “naturalized”.